Performance Budgeting - Costing Principles - Kowalczyk, Magdalena (Studia Oeconomica Posnaniensia, 2013)
The purpose of this article is an attempt to present the possibility of using improved accounting principles for costing tasks in performance budgeting. The biggest problem with performance budgeting is the correct settlement. Consideration needs to be given as to which solutions should be chosen to fully take advantage of performance budgeting. The article consists of three parts. The first part of the study is based on a review of the literature, which shows the advantages and disadvantages of budgeting. Th e second part of the article shows what changes could be made to the accounting records to better perform the cost calculations for individual tasks. Finally, the third and last part discusses the principles of cost calculations used in performance budgeting as well as showing the benefi ts to be gained through the use of this method of accounting for expenditures on the implementation of tasks.